Creation of vector marks for robot navigation - Baranauskas, V.; Šarkauskas, K.; Bartkevičius, S. (Elektronika ir Elektrotechnika, 2008)
Usage of electrostatic field or artificial potential functions, trajectories of movement are far from optimal path, because in some cases movement is executed receding from the goal. So it’s necessary to find new methods for trajectories planning. Algorithm to determine virtual vector marks, representing environment, which is used for purposes of robot navigation is introduced. Simulated example with generated vector marks is placed. Authors of the article refer to previous works concerning problems of trajectories planning and calculations. Ill. 5, bibl. 4 (in English; summaries in English, Russian and Lithuanian).